The role of multilateral organizations in the development of education in Nigeria (2006)
The contemporary International Scene is full with numerous co-operations, understandings, undertakings and agreements of various forms of integration which are regional, Continental and global both in nature and dimension. All these integrations are essentially geared towards the elimination of ignorance and poverty. Such undertakings therefore revolves round almost all facets of human activities, military scientific, educational, cultural, health and a lot of others related activities. This interdependent complexity has unavoidably mode the numerous “development roles” of these fortified multilateral agencies inevitable especially to the developing countries. Nigeria as developing country faces both the new challenges of supporting knowledge-driven development and the old challenge of promoting quality, efficiency, and equity at all levels of her educational System. Giving these massive challenges and the obvious limitation facing the government in the revitalization of the system, with the consequence of eroding educational quality, it will therefore not be out of place for these multilateral organization such as the World Bank to lend their supporting hands to salvage the nation ’s failing educational system. The issue of multilateral assistance to educational development must go beyond lip service and international politics to a real and pragmatic support that will bring about sustained quality improvement in the Nigerian educational System. The International donors must pay serious attention to the provision of both financial and other forms of support to the Nigerian Educational System in order for the sector to compete with the ever dynamic global challenges. The educational sector as an important pivotal of economic growth and development. need a wholesale support from all and sundry. Since the ability and role of Government is constrained in most developing countries, multilateral agencies must relax stringent conditions to aid the educational development programmes of these countries